Maternal mortality due to obstetric cause in San Bartolome Maternal and Children's Hospital - Ludmir Grimberg, Abraham (1989)
We present our 25 years of experience in maternal mortality in Hospital Materno Onfantil de San Bartolome rebuilt in 1961, and dedicated to medical education and attention of a low socio-economic level of community. The obstetric and ginecology resident training program in Peru was started in this Hospital with preventive technology and philosophy, in agreement with the principles of continuos medical education utilized abroad in developed countries. Our maternal mortality was 5.27/10000 deliveries in recent years, low when compared with other peruvian hospitals with same characteristics. Firm teaching attitudes are necesary in our country to lower maternal mortality rates (An Fac Med UNMSM II Epoca 1989; 1 (1-2): 49-54).